The Legal Status of Taiwan in United State Courts - HSIEH, Pasha L. (Institutional Knowledge at Singapore Management University, 2009)
In 1979, the United States government terminated its official relations with the Republic of China and switched recognition to the People's Republic of China. In the same year, the United States Congress passed the Taiwan Relations Act (TRA) with the aim of protecting Taiwan from negative legal consequences which may stem from the withdrawal of recognition. After nearly thirty years, U.S. courts have established the principle of treating the TRA as the legal basis in dealing with the status of Taiwan. The courts have consistently considered Taiwan as a state regardless of the U.S. government’s termination of diplomatic ties. Hence, Taiwan has been able to possess state status under U.S. law, invoke the Foreign Sovereign Immunities Act and the act of state principle, retain its state assets in the United States, and assert an independent legal status from China under treaty obligations. The jurisprudence established by U.S. courts not only respects Taiwan's state status and sovereignty, but also exerts a positive impact on Taiwan-U.S. relations.